IDENTIFIKASI KESULITAN GURU MATEMATIKA SMP NEGERI SE-KOTA SELONG DALAM MELAKSANAKAN KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) - Zainal Abidin; Masjudin Masjudin (Lembaga Penelitian dan Pendidikan Mandala, 2016)
The purpose of this research is to identify the difficulties of Mathematics Teachers of SMP Negeri in Selong City in implementing Education Unit Level Curriculum (KTSP). Data collection techniques in this study using a questionnaire filled by respondents (math teacher SMP). The instrument of this study is a questionnaire containing questions that have been provided answers and respondents (math teachers) just choose, as well as some open questions that give the opportunity to respondents to answer with his own sentence. Statistical methods used are descriptive statistics in accordance with the form of research